Improving violence risk assessment and intervention in first episode psychosis - Whiting, D (2021)
Background Clinical care is often guided by prognosis. Understanding the chances of future outcomes associated with a health condition can inform decisions around support and treatment for individuals, and decisions at a clinical service or policy level. There is wide interest in refining individualised prognostic understanding to personalise care and inform stratified treatment, where interventions are targeted for maximum benefit. Prediction models are a key part of this progress. These models combine information about predictors of an outcome into a statistical model to estimate the risk of that outcome for an individual, and have had a substantial impact on clinical practice in areas such as cardiovascular medicine. However, many models that are developed are never adopted into practice. This can be due to limitations in development study methodology, or neglect of the stepwise process of translating into a usable clinical tool. Ideally, this should involve validating the accuracy of the model in a clinical setting, and considering practical issues such as its acceptability, feasibility and role.